Estimulación oportuna: ventajas para el desarrollo de su hijo - Natalia Salas-Guzmán; María Ester Morales-Ramírez (Universidad Nacional, Costa Rica, 2011)
Early stimulation presents as it's principle that "the earlier the child learns, better and more advantages he/she will obtain from the future" (Bravo and Pons, año 1, Nº5, p.66). The family, as a unique and first encounter for the child, supplies a fundamental role in the structure and development of the child's personality, presenting itself as main environment where the child is educated and stimulated; therefore, early stimulation starts at home. The present article establishes the importance of early stimulation in children's objectives for life, in it's development and educational compounds, showing the five sense in wich it can be worked, and explaining the highly significant role that the parent has in integral development of the personality in the child, in it's physical, cognitive, psychological and social areas.